Secondary and Higher School Succession Examplified by the School Geometry Teaching - G. A. Klekovkin (Образование и наука)
The paper analyzes the content of school geometry education; a number of reasons behind the degrading level of geometry training of secondary school leavers being discussed. The author argues that, in spite of the decline of the geometry research in modern mathematics, its educational and practical significance is growing along with the development of knowledge and technology. The author welcomes the introduction of elective courses in profile schools (e.g. solving geometrical problems based on the vector method, representation of geometrical figures in a parallel projection, etc), and regards it as the important means of content succession and continuity of mathematical education in secondary and higher schools; the problems of content and teaching method selection for given courses being discussed providing the effective link between the profile and professional education.The research findings can be of interest to the experts in mathematical teaching methods, elective course developers and school teachers of mathematics.